Phylogenetic and population genetic studies in the genus Streptocarpus Lindl. (Gesneriaceae DC.) - De Villiers, Margaret Jenifer (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Botany and Zoology))—-Stellenbosch University, 2008.